GREENHOUSE GASES EMISSION INVENTORY OF POLLUTANT CO2 FROM TRANSPORTATION ACTIVITIES IN NORTH BANDUNG AREA - ARDIANSYAH (NIM 15304014); Pembimbing: Ir. Raden Driejena, MSCE., Ph.D., YUDHI
transportation sector is one of the biggest contributor of green house gases today. The usage of fossil fuel as energy source for machine activation, produce few kind of green house gases. From fossil fuel burning process in vehicles, it will produced the significant green house gases such as carbon dioxide (CO2), methane (CH4), and Nitrogen oxide(N2O). emission inventory can be used for government assessment reference in mitigation efforts toward climate change effects. By means of this inventory we can know the contribution of transportation sector toward pollutant load, in this case are CO2 in the North Bandung area. This research concern to roads including to Bandung Utara region with object motorcycles, Four wheels vehicles (cars and buses), and trucks. The counting of emission load of green house gases (CO2 and CH4) done by distance approach. First of all, transportation surveying done in research area to get vehicles activities data in form of vehicles volume and average velocity of vehicles. Transportation survey done at weekday and weekend condition. Then England emission factor database was chosen to count emission load result. Based on the result of transportation survey and load counting we have known that road with high traffic is Jalan Djuanda and we knew that this road produced highest emission load. That make we knew that emission factors is significantly affected into emission load value. England emission factor database was used because it was the emission factor which had the best possibility to applied because of the detail is suitable for our needs and fields condition. It makes this database give better emission load value.